Viver a sexualidade com o corpo ferido: representações de mulheres e homens - Carvalho, Evanilda Souza de Santana (2010)
Banca Examinadora: Mirian Santos Paiva, Maria Elena Casado Aparício, Cecília Maria Bacellar Sardemberg, Edméia de Almeida Cardoso Coelho, Dora Sadigursky, Fernanda Carneiro Mussi e Maria da Penha Lima Coutinho.